Wound Healing - Current Perspectives 2019
DOI: 10.5772/intechopen.80978
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone (GH) and Wound Healing

Abstract: Wound healing is complex and numerous factors overlap perfectly with the goal of wound closure. Among them, we will focus on a large amount of experimental and clinical evidence on the action of GH in wound repair. We will analyze how the physiological rhythm of GH secretion influences this process, and also one of the most important signaling pathways that mediate the effects of GH on tissue regeneration. The role of IGF-1 and the factors that stimulate GH secretion and that have also been shown to improve he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 135 publications
(174 reference statements)
0
3
0
Order By: Relevance
“…Noteworthy among these factors are vascular endothelial growth factor (VEGF), Fibroblast Growth Factor (FGF), and Stromal cell-Derived Factor-1 (SDF-1), collectively orchestrating tissue regeneration and angiogenesis. GH, functioning as a regulatory maestro, elevates the expression and availability of these growth factors, thereby fostering an environment optimally conducive to accelerating wound healing [ 27 ]. In another study, independent of GH, clonidine demonstrated an increase in VEGF and VEGF receptor expression, along with a concurrent reduction in lung inflammation, ultimately culminating in the amelioration of lung tissue repair [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy among these factors are vascular endothelial growth factor (VEGF), Fibroblast Growth Factor (FGF), and Stromal cell-Derived Factor-1 (SDF-1), collectively orchestrating tissue regeneration and angiogenesis. GH, functioning as a regulatory maestro, elevates the expression and availability of these growth factors, thereby fostering an environment optimally conducive to accelerating wound healing [ 27 ]. In another study, independent of GH, clonidine demonstrated an increase in VEGF and VEGF receptor expression, along with a concurrent reduction in lung inflammation, ultimately culminating in the amelioration of lung tissue repair [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GHAS study, a phase III randomized controlled trial, was designed to test the benefit of low dose of GH (0.4 mg per day, 5 days a week, during 2 months) for wound healing and rest pain relief in CLTI patients compared to placebo or control group, in which an injection of serum was administered with the same protocol instead of GH [ 28 , 29 , 30 ]. Blood samples were extracted for the determination of plasma biomarkers at the beginning of the study (basal) and after two months of treatment initiation (final).…”
Section: Methodsmentioning
confidence: 99%
“…From January 2016 to December 2018, all patients with diagnosis of CLTI who met inclusion criteria were enrolled in the Growth Hormone Angiogenic Study (GHAS) trial. The GHAS study, a phase III randomized controlled trial, was designed to test the benefit of low dose of GH for wound healing and rest pain relief in CLTI [27][28][29]. Blood samples were extracted for the determination of plasma biomarkers at the beginning of the study (basal) and after two months of treatment initiation (final).…”
Section: Methodsmentioning
confidence: 99%